- Perbandingan Penerapan Predatory Pricing Menurut Hukum Persaingan Usaha Indonesia dan Amerika Serikat: - - Farhandi Himawan; Anna Maria Tri Anggraini (Reformasi Hukum Trisakti, 2023)
Entrepreneurs engage in the practice of "selling and loss" in order to eliminate their rivals. Each nation has its own laws governing the proscription of selling at a loss. The formulation of the issue is the parallels and discrepancies between Indonesian and American laws governing sales and losses, business competition, and the application of the ban on predatory pricing based on KPPU-P Decision No. 03/KPPU-L/2020 and Brooke Group Ltd. v. Brown & Williamson Tobacco Corp. Legal normative approach opposed to legal comparison between Indonesian and American law. utilizing secondary qualitative data and inference. The findings of the study and discussion show that it is governed in Indonesia by Article 20 of Law No. 5/1999, while In the United States, agreements including predatory pricing are prohibited by Section 2 of the Sherman Act and Section 2(a) of the Clayton Antitrust Act. In terms of the business competition authorities in Indonesia and the United States, KPPU, DOJ, and FTC are autonomous Indonesian organizations. Only one authority in Indonesia, namely KPPU, is in charge of business competition matters, although DOJ and FTC are present in the United States. In conclusion, Indonesia and the United States are required to take into account economic theories.